2000
DOI: 10.1007/s00223001099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Bone and Calciotropic Hormones in Growing Female Rats

Abstract: Limited research in young adults and immature animals suggests a detrimental effect of tobacco on bone during growth. This study investigated the effects of nicotine, the major alkaloid component of tobacco, on calciotropic hormone concentrations and bone status in growing female rats. One-month-old animals received either saline (n = 10), nicotine at 3.0 mg/kg/day (n = 10), or nicotine at 4.5 mg/kg/day (n = 10) administered subcutaneously via osmotic minipumps for either 2 or 3 months. Sera, femora, tibiae, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
2
39
1
2
Order By: Relevance
“…However, vertebral and femoral mass and strength were little affected by nicotine treatment in either the intact or the OVX rats. The results [7,8,14,26] suggest that tobacco agents other than nicotine are responsible for the decreased bone density and increased fracture risk observed in smokers [6,12,17,18,23,24]. This study's limitation was that it investigated nicotine effects after bone loss had been established.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, vertebral and femoral mass and strength were little affected by nicotine treatment in either the intact or the OVX rats. The results [7,8,14,26] suggest that tobacco agents other than nicotine are responsible for the decreased bone density and increased fracture risk observed in smokers [6,12,17,18,23,24]. This study's limitation was that it investigated nicotine effects after bone loss had been established.…”
Section: Discussionmentioning
confidence: 97%
“…Such high doses were used because treatment of rats with nicotine at serum concentrations within the range observed in smokers had no effect on the biomechanical properties of bone [7,8,14,26]. However, treatment of rats with nicotine at serum nicotine concentrations 2.5-fold greater than that found in smokers resulted in lower femoral size and ultimate load (fracture load), suggesting that nicotine, at high intakes, may compromise bone mass and strength [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that nicotine may have a priming effect in calcium metabolism and regulation during lactation with possible programming consequences in calcium hormonal regulation in adulthood, because nicotine administration in female rats results in lower serum calcitriol with no differences in serum Ca C or PTH (Iwaniec et al 2002) and because serum cotinine (a nicotine metabolite) has a significant inverse relationship with bone mineral content in a clinical study (Benson & Shulman 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the best experimental evidence for the negative effect of nicotine on bone derives from studies of bone metabolism following injury. In the rabbit fracture healing model, several investigators have found that bone graft vascularization and subsequent bone formation is reduced with nicotine treatment 8 . In the present study, the lack of significant differences regarding the other parameters investigated (BA, BW, BH) may in part be due to the random sampling variability.…”
Section: Discussionmentioning
confidence: 99%